Platform work, exploitation, and migrant worker resistance: evidence from Berlin and London - Alyanak, O; Cant, C; López Ayala, T; Badger, A; Graham, M (Cambridge University Press, 2023)
For migrant workers who do not have access to other means of income, the platform economy offers a viable yet exploitative alternative to the conventional labour market. Migrant workers are used as a source of cheap labour by platforms – and yet, they are not disempowered. They are at the heart of a growing platform worker movement. Across different international contexts, migrants have played a key role in leading strikes and other forms of collective action. This article traces the struggles of migrant platform workers in Berlin and London to explore how working conditions, work experiences, and strategies for collective action are shaped at the intersection of multiple precarities along lines of employment and migration status. Combining data collected through research by the Fairwork project with participant observation and ethnography, the article argues that migrant workers are more than an exploitable resource: they are harbingers of change.